Development Of Mobile-Based Learning Media Using The Construct 3 Application In Informatics Subjects - Angga Wicaksono; Fahrur Rozi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The development of technology has affected the world of education in the content of the material and the learning process. At SMP Negeri 1 Besuki, it is known that technology-based learning media has never been developed during learning. The learning media that runs at SMP Negeri 1 Besuki is considered boring for students. This learning media is expected to help students to understand learning independently and improve the ability to understand informatics subjects.This research uses the ADDIE development model which consists of five stages, namely: analysis, design, development, implementation and evaluation. The ADDIE model provides an opportunity to evaluate development activities at each stage, this has a positive impact on the quality of development products. Based on the results of the feasibility test from the media expert of 83.63%, the results of the feasibility test on the material test amounted to 84.44% and student respondents amounted to 82%. If calculated the average is 83, 35%. Based on the criteria guidelines above this product is declared